PENGARUH STUDY FROM HOME (SFH) DALAM PEMBELAJARAN ONLINE BAGI PESERTA DIDIK KELAS 12 IPS III SMA N 2 KOTA SEMARANG DALAM MENGHADAPI PANDEMIK COVID-19 DI KOTA SEMARANG - Vincent Berliandis Salempang Utomo (Universitas Muhammadiyah Tapanuli Selatan, 2020)
Health is very important for every human being in the world, especially in the face of the co-19 pandemic period especially in Indonesia. and therefore the Indonesian government imposed a number of policies including the School From Home (SFH policy on the implementation of the Work system. The purpose of this discussion is to measure how much effect the SFH policy has on reducing the spread of Covid-19.This research is a quantitative research survey with this discussion expected to be able to explain how much the influence of SFH in online learning As a conclusion is the effect of SFH for IPS III students of SMA N 2 Semarang City does not provide great influence in the learning system. Further research in this issue is needed to be an appropriate suggestion for the next step.